The effect of book tax differences and total asset turnover on profit growth with company size as a moderating variable - Prindiaznova Putri, Cindy; Hidayati, Wahyu Nurul (Educoretax, 2024)
This research is entitled The Effect of Book Tax Differences and Total Asset Turnover on Profit Growth with Firm Size as a Moderating Variable. This research aims to empirically test and prove the influence of Book Tax Differences and Total Asset Turnover on Profit Growth moderated by Firm Size for Energy Sector companies listed on the Indonesia Stock Exchange in 2018-2022. This research was conducted using quantitative methods and the sampling technique used was purposive sampling. The population in this research is all energy sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The number of companies used as research samples was 7 companies. The results of this research indicate that book tax differences and total asset turnover simultaneously have a significant effect on profit growth. Meanwhile, the result of research partially proves that only the book tax differences variable has an effect on profit growth. Firm size as a moderating variable is able to strengthen the influence of book tax differences on profit growth. However, firm size does not strengthen or weaken the influence of asset turnover on profit growth.